Current advances in molecularly imprinted polymers and their release mechanisms in drug delivery systems - Vannessa, Lawai; Zainab, Ngaini; Saba, Farooq; Rafeah, Wahi; Showkat Ahmad, Bhawani (John Wiley & Sons, Inc, 2024)
Molecularly imprinted polymer (MIP) has gained wide interest among researchers due to its unique molecular recognition of the template that is suitable as a drug carrier. Therefore, the preparation and formulation of the MIP are significant to suit the needs of the intended use. Due to its significance in drug delivery, this review aims to highlight various methods in the preparation of MIP, the composition for both controlled and stimuli-responsive drug delivery systems, and the release mechanism of the drugs. In drug delivery systems, MIP should have a sustained release performance as well as flexibility in surface modification for targeted delivery via a range of stimuli-responses, including external stimuli (magnetic, light) and internal stimuli (pH, temperature, redox, biological). The properties of sustained release and targeted delivery of the MIP can improve the drug's therapeutic efficacy as well as the breakthrough for the tumor targeting application.